(untitled) (Kashf Journal of Multidisciplinary Research, 2024)
As technological advancements and global challenges continue to reshape society, the role of education in preparing students for an uncertain future is more critical than ever. This paper explores how education systems must evolve to equip learners with the skills, mindsets, and adaptability needed for success in a world that is constantly changing. Focusing on future-proof skills such as critical thinking, creativity, collaboration, and digital literacy, the article analyzes how pedagogical strategies like project-based learning, experiential education, and artificial intelligence (AI) integration can prepare students for an unpredictable future. This paper argues that to teach the future, we must foster lifelong learners who can navigate the complexities of a rapidly evolving world and address both known and unknown challenges with innovative solutions..